Determination of Fe2+ and Fe3+ species by FIA-CRC-ICP-MS in Antarctic ice samples - Spolaor, Andrea; Vallelonga, Paul; Gabrieli, Jacopo; Cozzi, Giulio; Boutron, Claude; Barbante, Carlo (J. Anal. At. Spectrom., 2012)
n/a